2023
DOI: 10.1186/s13020-023-00800-1
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves gout arthritis pain via attenuating ROS-mediated NLRP3 inflammasome overactivation

Abstract: Background Gout results from disturbed uric acid metabolism, which causes urate crystal deposition in joints and surrounding tissues. Gout pain management is largely limited to colchicine and nonsteroidal anti-inflammatory drugs. Constant usage of these medications leads to severe side effects. We previously showed electroacupuncture (EA) is effective for relieving pain in animal model of gout arthritis. Here we continued to study the mechanisms underlying how EA alleviates gout pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 52 publications
(89 reference statements)
1
17
0
Order By: Relevance
“…We noticed in our recent studies that gouty arthritis model animals also developed obvious heat hyperalgesia 14 , 40 . AOS3 (200 mg/kg) treatment significantly alleviated heat hyperalgesia of model mice ( Figure S2 A&B).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We noticed in our recent studies that gouty arthritis model animals also developed obvious heat hyperalgesia 14 , 40 . AOS3 (200 mg/kg) treatment significantly alleviated heat hyperalgesia of model mice ( Figure S2 A&B).…”
Section: Resultsmentioning
confidence: 97%
“…The mice were anesthetized with 2.5% isoflurane during the injection. Ankle swelling and mechanical hypersensitivity, which would occur 2 h after MSU injection, were regarded as criteria for successful establishment of the model as reported 14 .…”
Section: Methodsmentioning
confidence: 99%
“…165 Inflammation during GA can expand without limitation, leading to joint necrosis and even death if there is no regulatory mechanism. 166,167 There is no doubt that multiple mechanisms are utilized to prevent endless inflammation from happening. Evidence has showed that several key mechanisms are involved in inflammatory regression during gouty arthritis.…”
Section: Inflammatory Resolutionmentioning
confidence: 99%
“…The methods were adopted from our previous study [35] . Brie y, the mice were sacri ced on day 7 or 14.…”
Section: Immuno Uorescence Stainingmentioning
confidence: 99%